The Effect of Attitudes on Behavior, Subjective Norms, Behavioral Control, Behavioral Intentions on Lecturer Behavioral: The Moderation Role of Compliance with Regulations and Visionary Leadership in LLDIKTI Region VI Central Java Indonesia - ., Praptiestrini; Brahmasari, Ida Aju; Mujanah, Siti (Journal of Ecohumanism, 2024)
Phenomenon, Private University at LLDIKTI VI Central Java (1) There is inequality in the quality of education which indicates that the increase in human resources has not been evenly distributed in all areas of the city/district. (2) The behavior of lecturers in carrying out tridharma activities is still not optimal. This research is based on the existence of empirical GAP and theoretical GAP regarding the limitations of TPB theory, so this research closes this gap by adding the variable compliance with regulations and visionary leadership as a moderator, which is combined into the Theory of Planned Behavior model to make this variable as research novelty. The aim of the research is to prove and analyze the influence of behavioral attitudes and norms subjective, behavioral control towards lecturer behavior through behavioral intentions and prove and analyze the role of regulatory compliance and leadership visionary in moderating influence of behavioral intentions to behavior lecturer. Study​ this is causal explanatory with a sample of 370 lecturers in LLDIKTI Region VI Central Java in 2022. Data collection techniques use questionnaires, data analysis uses SEM. Results research (1) behavioral attitudes influential significant positive to behavioral intentions. (2) behavioral attitude has no effect on lecturer behavior. (3) norms subjective influential significant positive effect on behavioral intentions. (4) norms subjective influential significant positive effect on lecturer behavior. (5) control behavior influential significant positive effect on behavioral intentions. (6) control behavior influential significant positive effect on lecturer behavior. (7) behavioral intention influential significant positive effect on lecturer behavior. (8) compliance on regulation moderate influence of behavioral intentions towards lecturer behavior. (9) leadership visionary moderate influence of behavioral intentions towards lecturer behavior.